Study of Palm Shell Biochar Capability in Absorbing Metals on Landfill Leachate - Hasnelly,; Yasin, Syafrimen; Agustian,; Darmawan, (International Journal of Psychosocial Rehabilitation, 2020)
Landfill leachate contains a variety of organic, inorganic and metal materials that are damaging to the environment. Leachate can contaminate water, soil and the surrounding environment, so it needs to be improved, such as a decrease in metal content in the leachate. Based on this, this research was conducted to reduce metal content in leachate by using biochar. This study aims to determine whether biochar palm shell can reduce metal content (Pb and Cd) in leachate. This research consists of II (two) stages. Stage I. Using a Randomized Block Design (RBD) consisting of 2 factors with three replications. Factor I: biochar size (U) consisting of U1 = 80 mesh; U2 = 120 mesh; U3 = 140 mesh; and U4 = 170 mesh. Factor II: biochar contact time with landfill leachate consisting of W1 = 1 hour; W2 = 2 hours; W3 = 3 hours. Stage II. Using a Completely Randomized Design (CRD) with five treatments and four replications. The treatment is: without biochar (B0), 20 g/L leachate (B1), 40 g/L leachate (B2), 60 g/Leachate (B3), and 80 g/L leachate (B4). The results of the first phase of research showed that there was an interaction. The best interaction on the use of 140 mesh biochar size with a contact time of 3 hours (U3W3). The result was a decrease in Pb metal content by 64.1% from 14.68 mg/L to 5,273 mg/L and 9.62 mg/L to 1,710 mg/L for Cd metal (82.2%). The results of the second phase of the study showed that increasing the dose of biochar can reduce the Pb and Cd metal content in the landfill leachate. The highest decrease in Pb and Cd metal occurred at 80 g/L biochar dose.